Obesity Is Associated with an Increase in Pharmaceutical Expenses among University Employees - Julie A. Gazmararian; David Frisvold; Kun Zhang; Jeffrey P. Koplan (Journal of Obesity)
Objective. To examine costs associated with obesity in an employee population and factors associated with increased costs. Methods. We used data from the Physical Activity and Life Style (PALS) study, a randomized prospective design evaluating three interventions to increase physical activity among physically inactive nonfaculty university employees (n=454). The primary exposure variable, obesity (measured by body mass index), was obtained from the in-person baseline survey. Covariates were obtained from the baseline survey and included demographic characteristics and health status. Data from the baseline survey was linked with administrative data to determine pharmaceutical, inpatient, outpatient, and total health care costs for three years. Average monthly expenditures for obese and nonobese individuals were compared using t-tests and a two-part multivariate regression model adjusted for demographic and socioeconomic characteristics and health behaviors. Results. Although in-patient and outpatient expenses were not associated with obesity, pharmaceutical expenditures were $408 or 87.2% higher per year ($468 versus $876) for obese individuals than for nonobese individuals, which reflected poorer health behaviors and health status of obese adults. Conclusion. Awareness of the costs associated with obesity among employees can stimulate employers to make the investment in providing employer-sponsored wellness and health improvement programs to address obesity.